PENGEMBANGAN SOFTWARE APLIKASI MATEMATIKA DAN STATISTIK UNTUK PERANGKAT BERGERAK - Mohammad Jamhuri (El-QUDWAH, 2010)
This paper discusses about the making of an application program in mathematics and statistics intended for use on mobile devices (cell phone). This paper also describes the process how the programs created to read the input provided by the user via the textbox and translated as a command to run a number of mathematical and statistical operations which is summarized in a function, and the results are displayed back through the textbox. Several simulations using software that has been made also provided at the end of this paper, including the procedures concerning orders to call the functions defined in it. The defined functions in this software has reached 200 functions consisting of Mathematics and Statistics functions.